The end of capitalism : destructive forces of an economy out of control - Parks,Robert H.. (New York : Prometheus Books, 2011)
U.S. capitalism has long been viewed as first among competing economies in productivity, job creation, wealth, power, and individual freedom. But the recent deep recession has left many questioning America's future and the long-term viability of capitalism in general. Shocking events in the investment banking and lending sectors that led to the 2008 financial meltdown were soon followed by numerous government and Federal Reserve efforts to stabilize the economy. Yet Americans continue to suffer in the grip of massive home foreclosures, job losses, and political leaders at loggerheads about what should be done. These grave economic and political circumstances are the catalyst for a candid, sobering assessment of our social situation. And no one is better suited to perform this vital task than noted market watcher, Federal Reserve observer, and macro economist Robert H. Parks, who teas studied capitalism and its effects for decades and is convinced that in its unrestrained capitalism is rushing headlong toward its own demise.
Includes bibliographical references and index.
Keywords: Capitalism; Economic history